PTH-051 Impact of a dedicated barrrett's oesophagus list on reducing surveillance endoscopies and cost implications. (17th June 2017) - Hussaini, SI; Peart, J; Fracasso, G; Austria, M; Agyemfra, I; Gupta, S
Abstract : Introduction: Barrett's Oesophagus (BO) is a risk factor for oesophageal adenocarcinoma (OAC). London Cancer Alliance published guidelines for dedicated Barrett's surveillance list with advanced imaging techniques which was adopted by Croydon in June 2015 with a single operator monthly list. While the focus was on identifying dysplasia/early cancer, we opted to analyse the impact of a dedicated surveillance list on patients with a low risk of cancer progression who could be discharged back to primary care and the potential cost savings that could be made. Method: We analysed a prospective database of all patients who had a gastroscopy on a dedicated BO surveillance list from June 2015 to December 2016. Patients with <2m BO without intestinal metaplasia (IM) on histology were discharged back to primary care. Based on the life expectancy of males being 78 years and females 82 years (2015), average cost savings for endoscopy every 5 years was calculated based on the tariff in 2016. Results: Out of 85 patients, 62 (73%) were males. Average age for males was 65 and 68 years for females. All patients had PPI as regular treatment. 59 (69%) patients had IM, The mean Prague 'C' length was 1.9 cm while 'M' was 3.6 cm. Four patients had indefinite for dysplasia out of which 3 were referred to tertiary care centre and 1 was downgraded on repeat endoscopy. One patient had OAC. 20 (24%) patients with <2 cm BO with no IM were discharged from surveillance. Based on a tariff of £420 for gastroscopy with biopsies, 34 gastroscopies in males (£14280) and 30 in females (£12600) were avoided thus resulting in cost savings of about £27 000 on the assumption that surveillance would have continued till their life expectancy with the tariff remaining the same. Conclusion: We recognise that the patients who were taken off the dedicated surveillance list may have been taken off anyway if they had an endoscopy on a normal service list. However assessment of these patients on a dedicated list has ensured uniformity of follow-up surveillance endoscopy and discharge. Lack of awareness and adherence to updated guidelines by various grades of health professionals might have resulted in unnecessary endoscopies. There are potential cost savings although it would be difficult to quantify them accurately because of variable factors. Strict adherence to guidelines would also increase capacity for endoscopy units in the face of rising demand. Disclosure of Interest: None Declared